THE EASTERN PHILOSOPHER AND THE WESTERNIZED PROPHET - Tchaparian, Vicky (Armenian Folia Anglistika, 2021)
Gibran Khalil Gibran is one of the few Lebanese authors who has bridged the East and the West and is justifiably considered a citizen of the world. His book of highly estimated prose poems, The Prophet is one of the most widely read books of the 20th century. It reveals Gibran’s philosophy about different aspects of life, mainly the precept in the Gospel of Matthew about the importance of the human sense of mutuality which summarizes a Christian’s duty towards his/her neighbor and states a fundamental ethical principle. In addition to this golden rule, The Prophet reflects Gibran’s beliefs in Christianity. Being a true mirror of the Sufi mysticism of Islam, it also shows his idealistic opinion on pantheism. From this perspective, the research will focus on the combination of his beliefs in Christianity, Islam, and pantheism in The Prophet, as well as his firm conviction in creating the united and unique structure of a Christian-Muslim synthesis which he deeply adhered to.
Keywords: Christianity; the Gospel; Sufi; Islam; the Quran; pantheism; Prophet Almustafa; East and West